The Role of Trade Unions in Employee’s Redressal of Grievances in H imachal Pradesh State Electricity Board - Parmar, j.S.; Singh, Mr. (Gyan Management Journal, 2010)
the basic pre-requisite to attain the necessary success in the field of rapid industrialization is to attain the of congenial atmosphere of co-operation between workers and employers. The urgent need for _:iroduction can be met only through stable labor force and by recognizing workers as respectable partner The present studyaimed at knowing the view points of workers, trade union leaders and - : ·:: 1erial personnel regarding the existing grievances handling procedure followed by the State Electricity : and the role of trade unions in settlement of worker’s grievances. For this purpose both primary and "" : -::ary data were used. Five circles of HPEB were selected randomly including the Head Office Vidyut :-. .;ri, Shimla for the study. All these circles fall under Shim la, Solan and Sirmour districts of the state of Pradesh. And a sample of 240 workers, 105 trade union leaders and 105 managerial personnel were -: .vith the help of random sampling technique. The information thus collected has been analyzed with the statistical tools and techniques.